Comparative morphological analysis of a Leopard frog complex in Colorado - Ward, Finnegan E., author; Bailey, Larissa L., advisor; Newmark, Elena R., committee member (Colorado State University. Libraries, 2026)
Hybridization is a unique conservation issue that can lead to reduced fitness and loss of local adaptation and may influence management practices, especially for species of conservation concern. The ability to distinguish hybrids with morphological features is helpful for wildlife managers but often requires confirmation via genomic information. The Northern Leopard Frog (Lithobates pipiens; NLF) and Plains Leopard Frog (Lithobates blairi; PLF) are two native species of leopard frogs in Colorado which are known to hybridize in areas where their ranges overlap in the southeastern region of the state. NLFs are listed as a Tier 1 species of conservation concern in Colorado, with significant population declines throughout the state but especially on the Front Range. In contrast, PLF populations are thought to be stable, and the species is not of conservation concern (CPW, 2026). The goal of this study is to determine the morphological characteristics that distinguish between NLFs, PLFs, and putative hybrid individuals. The Funk Lab and CPW biologists collected tissue samples and photographs of leopard frogs throughout Colorado. I randomly selected 20 individuals of each species and 4 putative hybrids for this study. Characteristics from sampled individuals were categorically scored on a variety of traits that are hypothesized to distinguish between the species. I used two analyses to evaluate traits that best predicted species identity: logistic regression and Random Forest computer learning algorithm. Both logistic regression and Random Forest suggest the tympanum spot is the best predictor of the NLF species, with the dorsolateral fold also showing importance for identification. Additionally, the Random Forest shows strong predictive ability between species, but accuracy is negatively influenced with the inclusion of putative hybrids. Eventually, we will be able to use genetic data to determine true species identity and whether hybrids can be identified morphologically. If they can, we will be able to establish the best combination of traits for field identification of species.
Keywords: amphibian; wildlife management; hybridization; random forest; morphology